2013
DOI: 10.1093/icvts/ivt522
|View full text |Cite
|
Sign up to set email alerts
|

Guideline adherence in antithrombotic treatment after concomitant ablation surgery in atrial fibrillation patients

Abstract: Real-life OAC prescription in AF patients showed a moderate guideline adherence, with high-risk patients being undertreated and low-risk patients being overtreated. These findings stress the importance that antithrombotic treatment in patients undergoing AF surgery needs to be critically re-evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…CHA 2 DS 2 -VASc score as a significant predictor of anticoagulant prescribing before catheter ablation in our population was observed. The higher CHA 2 DS 2 -VASc score was associated with a higher anticoagulation prescription preablation, which was inconsistent with the discovery by Bista et al 17,21 Furthermore, HAS-BLED score, age, hypertension, and diabetes mellitus were also related to the use of anticoagulant before catheter ablation. Although those factors were observed as negative predictors for anticoagulant prescribing after catheter ablation, we found that the higher CHA 2 DS 2 -VASc score was associated with less frequent prescription of NOACs, which may illustrate that practitioner reluctant to use a newer therapy for higher embolism risk patients.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…CHA 2 DS 2 -VASc score as a significant predictor of anticoagulant prescribing before catheter ablation in our population was observed. The higher CHA 2 DS 2 -VASc score was associated with a higher anticoagulation prescription preablation, which was inconsistent with the discovery by Bista et al 17,21 Furthermore, HAS-BLED score, age, hypertension, and diabetes mellitus were also related to the use of anticoagulant before catheter ablation. Although those factors were observed as negative predictors for anticoagulant prescribing after catheter ablation, we found that the higher CHA 2 DS 2 -VASc score was associated with less frequent prescription of NOACs, which may illustrate that practitioner reluctant to use a newer therapy for higher embolism risk patients.…”
Section: Discussionmentioning
confidence: 63%
“…8 Accordingly, those studies before 2017 were assessed by the consensus of 2012, which indicated irrational utilization of anticoagulation after ablation. 21,22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catheter ablation (CA) procedures performed in the left atrium (LA) or left ventriculum (LV) present a rather unique situation, encompassing risks of both significant bleeding and thrombotic events. According to the latest international guidelines, CA of AF should proceed without interruption of DOACs [ 7 , 60 , 94 , 95 ], and it is mandatory to utilize unfractionated heparin (UFH) before or immediately after the trans-septal puncture to reach and maintain a target activated clotting time (ACT) of at least ≥300 s [ 94 ]. As assessed in several studies [ 96 ], in patients with uninterrupted DOAC, often a greater amount of UFH is needed to reach the target of ACT ≥ 300 s, and the administration of a higher amount of heparin was associated with an increased rate of procedural major bleedings.…”
Section: Interventions With High Bleeding Risk and Increased Thromboe...mentioning
confidence: 99%
“…This is also true for oral anticoagulants (OACs), which often require lifelong treatment. Many studies have explored the short- and long-term adherence rates of OAC among patients with AF or VTE in real-world settings [ 163 ]. The adherence rate in OAC users ranges widely depending on the setting and patient characteristics and decreases over time [ 164 ].…”
Section: Adherence To Oral Anticoagulant Intakementioning
confidence: 99%